Data linkage of routinely collected electronic health records to characterise risk factors associated with antibiotic resistance in urinary isolates: an exemplar of NHS Scotland's Infection Intelligence Platform. (2017) - Fletcher, Eilidh; Kavanagh, Kim; Malcolm, William; Wiuff, Camilla; Reid, Nicholas; Deshpande, Ashutosh
No abstract available